A study on the cognitive development of media literacy and its influence in limiting media effects. - Aw, Nigel Heng Liang (2011)
In a society saturated by media messages, it is becoming increasingly difficult for audience to discern between positive and negative content. This is aggravated by the use of media knowledge to cleverly package media content to seem convincing and compelling. In such an environment, media literacy, the ability to critically analyse, evaluate and discern media content and its production is imperative. Through a survey of 200 degree students from Universiti Tunku Abdul Rahman (UTAR) Kampar, Perak, this paper attempts to construct a means to measure media literacy based on theories provided by several scholars in this field. A correlation is then established to media effects and media usage in relation to media literacy level. The research found that individuals with higher media literacy can cope better with media effects in terms of behavioural change though it is limited in terms of change of perception. Furthermore the paper also found indications that among an already media literate population, the individual media usage behaviour is more significant than conventional media education in building up media literacy. The results suggest that there should be a review in the way media literacy education is approached.